2015
DOI: 10.15376/biores.10.2.3378-3392
|View full text |Cite
|
Sign up to set email alerts
|

Study of Sound Absorption Coefficients and Characterization of Rice Straw Stem Fibers Reinforced Polypropylene Composites

Abstract: In this study, both untreated rice straw stem fibers and fibers treated with sodium hydroxide were used. Maleic anhydride polypropylene (MAPP) was used to enhance adhesion of the fiber with the matrix. Composites were prepared with various combinations of fiber, ranging from 10 wt.% to 25 wt.%, and polypropylene in addition to 2 wt.% MAPP. These composites were then tested for acoustical, mechanical, thermal, infrared spectral, and morphological properties. The fibers were treated by being soaked in 5 wt.% NaO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 26 publications
0
18
0
1
Order By: Relevance
“…These fiber reinforcements improve the mechanical strengths and thermal stability of the composites (Panthapulakkal et al 2006;Alemdar and Sain 2008;Zou et al 2008;Mominul et al 2009;Ravindra et al 2010;Arrakiz et al 2013). Most studies have demonstrated that natural fiber reinforcement in polymer matrices substantially improves the desirable characteristics of composite materials in engineering applications, demonstrating the advantages of these fibers over synthetic glass and carbon fibers (Panthapulakkal et al 2006;Jayamani et al 2015).…”
mentioning
confidence: 99%
“…These fiber reinforcements improve the mechanical strengths and thermal stability of the composites (Panthapulakkal et al 2006;Alemdar and Sain 2008;Zou et al 2008;Mominul et al 2009;Ravindra et al 2010;Arrakiz et al 2013). Most studies have demonstrated that natural fiber reinforcement in polymer matrices substantially improves the desirable characteristics of composite materials in engineering applications, demonstrating the advantages of these fibers over synthetic glass and carbon fibers (Panthapulakkal et al 2006;Jayamani et al 2015).…”
mentioning
confidence: 99%
“…The sound absorption measurement showed that the acoustic properties were closely related to higher fibre content. The changes in the peak of FTIR spectrum revealed the removal of lignin and hemicelluloses from the rice stem fibres [93]. Liu also assessed the flexural properties of BCB using rice stalk fibre as filler with bio-based adhesive (corn starch) serving as the matrix material.…”
Section: Rice Fibre Bio-composite Boardsmentioning
confidence: 99%
“…While the major findings based on the utilization of rice husk for BCB are rather extensive, the opportunities that may avail its stalk have not been fully tapped. This curiosity led Jayamani and his research group to study the performance of rice stalk filled BCB with maleic anhydride polypropylene (MAPP) serving as matrix materials [93]. Similar to what Chen et al did in 2015, the stalk was treated with 5% wt of NaOH at 30°C for 30 min, and then a combinations of 10 to 25% wt and 2% wt of MAPP was used.…”
Section: Rice Fibre Bio-composite Boardsmentioning
confidence: 99%
“…This material is suitable for applications such as construction of bridges, installation of internal tunnels during short period road construction and as parts in vehicles. Elammaran et al [10] studied on characterization of rice straw fibers treated with sodium hydroxide and the results showed that lower fiber content in composites were poorer in sound absorption compared to the composites with higher fiber content which had better sound absorption. Manigandan et al [11] studied the mechanical and acoustic properties of pineapple leaf fiber and it was proven that the fiber can be used reduce noise.…”
Section: Introductionmentioning
confidence: 99%